Antecedents and Consequences of Academic Pressure Among Faculty Members at World-Class Universities From Scopus Database: A Narrative Review - Laili Qomariyah; Dian Ekowati; Mohammad Fakhruddin Mudzakkir; Fiona Siska Dinda (Sakura Digital Nusantara, 2026)
World-Class University (WCU) is a goal for universities around the world, including those in Indonesia, to demonstrate excellence in various fields, resources, and faculty measured by all relevant criteria as well as academic excellence and quality, as evidenced by a range of achievements. Academic pressure is one of the challenges faced by faculty members in the context of achieving various academic goals, with a focus on the antecedents and consequences of this issue within the WCU. The purpose of this article is to identify and synthesize the antecedents and consequences of academic pressure on WCU faculty members using a narrative review approach. Data were obtained from the Scopus database using the keywords “international ranking,” “World Class University,” or “academic,” yielding a total of 376 articles, of which 141 were suitable for in-depth analysis start at 2005-2024. This study examined the antecedents of academic pressure, including external factors such as the Tri Dharma, scientific publications, administrative workload, and frequently changing policies, as well as internal factors such as self-efficacy, personal capacity, time management, and work-life balance and the ambivalent consequences that trigger stress, burnout, a decline in work-life balance, and a deterioration in academic quality; yet, on the other hand, they can also enhance faculty competence, strengthen research culture, and accelerate global competitiveness. This research provides a comprehensive conceptual framework grounded in empirical evidence to help policymakers and strategists design faculty management approaches that are more supportive and focused on long-term academic performance. The conclusion of this study is that the consequences of academic pressure on lecturers not only have a negative impact but can also be a trigger for lecturers to improve their performance. Based on the background, this study has a different focus from previous research, namely related to the antecedents and consequences of academic pressure on lecturers at world-class universities as a novelty.